2013
DOI: 10.5539/ijms.v5n1p157
|View full text |Cite
|
Sign up to set email alerts
|

Affective and Cognitive: Consumers Attitude toward Practicing Green (Reducing, Recycling & Reusing)

Abstract: Understanding consumers' attitude toward practicing green behavior is vital for business as well as environmental reasons. The purpose of present study is to examine the green practicing concept (reducing, recycling and reusing) in an academic context from affective and cognitive perspective. Sample consisting of 315 university students gathered and analyzed using structural equation modeling technique (SEM). Findings indicate that environmental emotion and environmental cognition were significantly related to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…Being asked to engage in green/pro-environmental behavior evokes an emotional response, which may be either positive or negative (Nameghi and Shadi 2013). Prior studies have found that being asked to participate in sustainability programs can elicit negative affect (Baker, Davis, and Weaver 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Being asked to engage in green/pro-environmental behavior evokes an emotional response, which may be either positive or negative (Nameghi and Shadi 2013). Prior studies have found that being asked to participate in sustainability programs can elicit negative affect (Baker, Davis, and Weaver 2014).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Individuals' emotions have direct impacts on their attitude formation (Edell and Burke, 1987). Nameghi and Shadi (2013) found that consumers' emotions related to the environment were significantly associated with consumers' attitude. The arousal of emotions in consumers can affect their attitudes (Yoo et al, 1998); emotional experiences can produce positive or negative beliefs, which in turn influence consumers' attitudes (Fishbein and Ajzen, 1975).…”
Section: Hypothesesmentioning
confidence: 99%
“…Waste separation, practising buyback centres and recycling and reusing household items (Zena et al, 2014) High income and education level favour the green movement and have concerns for food safety Purchasing and consuming organic food (Teng et al, 2011) Concern on solid waste management and readiness to adjust to new practices Bring reusable bag for shopping (Zen et al, 2013) Awareness (familiarity to energy-efficient labels), attitude (standpoint on energy-savings) and social norms (environmental lifestyles) Purchasing energy-efficient products and appliances based on energy efficiency labels (Zainudin et al, 2014) Perceived consumer effectiveness (environment related past experience behaviour, environment-related intentionbehaviour, willingness to pay, and regulatory support -separating household waste, being a member of environmental groups environmentally conscious consumer behaviour (purchasing biodegradable products, energysaving products, and products that are less harmful to the environment) (Ramly et al, 2012) Environmental emotions, environmental cognition (well-informed, understanding and knowledge on green practices), environmental attitude (general sense of favourableness or unfavourableness for green behaviour) Keeping materials out of the waste stream: reduce (minimising consumption), reuse (use again or repurpose used materials) and recycle (Nameghi & Shadi, 2013) The case studies generated three significant components of AP: (i) Energy Saving (APa), (ii) Waste Handling (APb) and (iii) Smart Consumer (APc). Personal Lifestyle (PL) manifests in the personal outlook and approach to life in relation to environmental consciousness (Abu Bakar et al, 2017aBakar et al, , 2017bBakar et al, , 2017cBakar et al, , 2018.…”
Section: Literature Reviewmentioning
confidence: 99%